Die Bodengesellschaften im Mündungsbereich der Kinzig (Oberrheinebene) - Eine Methode zur Erfassung landschaftsökologischer Gegebenheiten in Alluvialgebieten - Krause, Werner (ERDKUNDE, 1980)
The paper describes, in a geographical arrangement, the soils in a district of about 225 square kilometers in the plain of the Upper Rhine. There are 171 deep profiles available, which were dug up by a dredge. Examples are given in appendix VII. As many soils are of holocenic origin, the recent water courses offer a first principle of arrangement. Every area through which a river or brook has flowed, has produced its own soil. The latter always stand in clear connection with the movement of water. In the areas without water courses, where pleistocene deposits occur, soils developed in dependence on the relief and mineralogy of the substrate. A synopsis is given in appendix VIII and IX. Near the recent water-courses soils are influenced by ground-water. They are permeable and suitable for various agricultural uses. A shallow depression with argillaceous sediments, where the high water often stagnates, offers bad conditions for agriculture. The pleistocene deposits, which are represented by gravels and loess, produced lessivated brown earth and pseudo-gley. Extreme conditions of habitat are given in an area where an impermeable layer of clay is superposed on ascending ground water. The results uncover, below a seemingly monotonous plain, a clear mosaic of soils. The latter gives information about local conditions of habitat, especially about water supply for plants. Simultaneously it opens an insight into prolific interrelations in the structure of the landscape.